Communalism : handled with a difference - Maheshwari, A. P. (New Delhi, 2000)
The book will be very useful for those who are willing to understand the causes leading to communal violence, immediate possible measures taken to control communal riots, direct and indirect repercussions of the riot break-outs, effective administrative and managerial measures to curtail and even prevent riots, possible measures for permanent solution to the communal riots and related problems.
Keywords: Communal riots